Urban multilingualism in Russian regions: linguistic landscapes and attitudes towards languages (the cases of Kyzyl and Ulan-Ude) - Khilkhanova, Erzhen V.; Tsybenova, Chechek S.; Ivanov, Viacheslav V. (The New Research of Tuva, 2024)
The article examines the attitudes toward languages among residents of the capitals of two Russian regions — Republic of Tuva (Kyzyl) and Republic of Buryatia (Ulan-Ude) — through the lens of linguistic landscapes and communicative practices. A semi-structured interview method was used, with a total of 30 interviews conducted among urban residents and business owners in 2021 and 2023.The study revealed that, despite the heterogeneous linguistic environments in Kyzyl and Ulan-Ude, the general trend leans toward proficiency in Russian, especially among children and youth. Similarities in visual linguistic landscapes and attitudes toward languages in Kyzyl and Ulan-Ude were noted. Differences in communicative practices among the residents of the two cities were also documented. In Kyzyl, the unwritten rules and conventions regarding language use in urban public spaces are currently in a state of transformation, whereas this shift took place in Buryatia during the Soviet era.Today, the normative use of Russian in the public sphere is combined with the “marked” use of Tuvan and Buryat. The communicative practices described in the article are interpreted within Pierre Bourdieu's concept of habitus.A contradiction is observed between the desire to see Tuvan and Buryat languages in the linguistic landscape and the lack of action in this direction by most business owners. This contradiction can be explained by several factors, including the divergence of interest between business owners and city residents. Business owners tend to favor commodification and pragmatic strategies in the naming of their establishments, while residents' desires are driven by cultural-symbolic and identity-related motivations. In theoretical terms, this can be described as a conflict between the symbolic value of the native language and habitus.
Keywords: urban multilingualism; linguistic landscape; language attitudes; communicative practice; communicative norm; naming; Kyzyl; Ulan-Ude; Tuvan language; Buryat language